Religion: The Final Frontier of the Rainbow Nation - Scharnick-Udemans, Lee-Shae Salma (Religion & theology, 2020)
Abstract This article assesses the ways in which religious diversity and religious pluralism are asserted and negotiated within the context of contemporary South Africa through scrutinising the Christian Friendly Products campaign which advocates against the ubiquity of the halaal food symbol and halaal food in South Africa. Halaal is an Islamic term, which refers to food products that are ritually permissible for consumption by Muslims. The campaign claims that the visible presence of halaal food in public spaces undermines the rights of Christian consumers, is an affront to the beliefs of Christians, and is a presage to the impending Islamisation of South Africa. In claiming that religion is the final frontier of the rainbow nation, this article argues that the myth of rainbowism, once wielded as a peacemaking gesture and nation building tool, has projected inaccurate representations of religious coexistence and difference in South Africa that obscure and minimise growing religious conflict and tension.